Eksistensi Peraturan Mahkamah Agung Nomor 02 Tahun 2012 Tentang Penyesuaian Batasan Tindak Pidana Ringan Dan Jumlah Denda Dalam KUHP - N. Okamahendra (Jatiswara, 2017)
This research to know and analyze the existence of PERMA No. 02 Year 2012 on Adjustment of Limitation of Criminal Act and Number of Penalties in Criminal Code with limited scope to review and analyze the existence of PERMA No. 02 Year 2012. This research is normative law research. The approach used is the approach of legislation, conceptual approach, philosophy approach, and case approach. Technique of collecting legal material with literature study. After that the processing of legal materials by systematization and then done logical, systematic, and interpretative reasoning with analytical descriptive analysis and draw deductive conclusions. Substantially the provisions in PERMA No. 02 Year 2012 has converted the concept of Criminal Crime especially on the limit of object value of loss of case to Rp. 2.500.000, - (two million five hundred thousand rupiah) and or a fine of up to seven million five hundred thousand rupiah and minor insult. The Articles of the Penal Code converted in the PERMA are 364, 373, 379, 384, 407 paragraph (1) and 482 of the Criminal Code. The position of PERMA in the hierarchy of the Laws and Regulations in Indonesia is as an internal regulation because of its binding power which only covers the environment of an institution so that it has no validity for other agencies and has juridical consequences.